Chemical Properties and Antioxidant Capacity of Elaeagnus angustifolia L. Fruits - Cansev, A.; Sahan, Y.; Celik, G.; Taskesen, S.; Ozbey, H. (Asian Journal of Chemistry, 2011)
Elaeagnus angustifolia L. (oleaster) is an autumn fruit which is generally consumed dried. Although it grows almost everywhere in Turkey, use of its fruits is limited. We analyzed chemical composition and antioxidant properties of the edible parts of Elaeagnus angustifolia L. fruit. Total moisture, ash, protein, total soluble sugar, fat, crude fibre, total titratable acidity and major mineral content of the fruit were determined. Total polyphenols were investigated using Folin- Ciocalteau method and antioxidant capacity of the fruit was assessed by scavenging 2,2-diphenyl- 1-picrylhydrazyl (DPPH) in the mesocarp and exocarp tissues. Results showed that potassium is the most abundant mineral in the fruit (8504 mg/kg) which is followed by sodium (1731 mg/kg) and phosphorus (635 mg/kg). Elaeagnus angustifolia L. fruit is a rich source of both several nutrients and antioxidant compounds. Average total phenolic content of aqueous, acetone and methanolic extracts of the mesocarp and exocarp in oleaster fruit were measured as 778 and 559, 390 and 361 and 414 and 524 mg gallic acid equivalents of 100 g-1 dried mass, respectively. In conclusion, E. angustifolia fruit is a rich source of chemical compounds and has a high mineral content. This fruit can be included in dietary products due to its possible health benefits.